The influence of natrural fermentation on coffee drink quality - Pereira, Leandro Ferreira Bernardes; Barbosa, Camila Karen Reis; Franco Junior, Kleso Silva (Coffee Science - ISSN 1984-3909, 2020)
Coffee quality refers to various methods used in farming, selective harvesting that assist in quality preservation and drying methods to be performed. Some drying methods that are being performed fermentation procedures have helped in obtaining specialty coffees. The objective of the research was to evaluate the effects of controlled natural fermentation of coffee through the temperature and time and its influence on the quality of coffee, according to the prescribed attributes in SCAA methodology, the type of coffee drink and time for drying grain. The research was carried out at Lavrinha farm, located at Poço Fundo (south of Minas Gerais), with coffee fruits of Catuaí Vermelho IAC 144 cultivar and selective and manual harvesting. The treatments with temperature-controlled fermentation of 30 and 40 °C (1, 2, 3, 6 and 12 hours) and the control treatment were used with three replications in a randomized block system (DBC) in a factorial scheme. After fermentation, the batches were dried to 11.5% humidity and evaluated according to the SCAA (2015) methodology. The natural fermentation induced by temperature (°C) and time (hours) directly influenced the drink quality, resulting in a coffee with a score of 82 to 84 points, with attribute aggregation and special classification. Natural fermentation with temperature up to 40 °C and time control of 3 ,1 and 24 hours resulted in an improvement in coffee quality by 84 points. Key words: Control; Drying; Harvest; Monitoring.